Differences in enteral nutrition on weight gain and length of stay of premature LBW at Kraton Hospital, Pekalongan Regency - Ayu, Gista; Chabibah, Nur (Indonesian Journal of Perinatology, 2024)
Introduction: Premature birth and low birth weight are major risk factors for infant mortality. The lower the birth weight, the higher the risk of mortality. Providing nutritional intake is very important for the survival of premature babies. Types of enteral nutrition that can be given are breast milk, HMF breast milk, and formula milk. This study aims to determine the difference in enteral nutrition on weight gain and length of stay of premature LBW. Method: This is a cross-sectional study with a simple random sampling technique—data from medical records of premature LBW babies from 2019 to 2023. Results: There was no significant difference between the type of enteral nutrition given on weight gain, both in the type of enteral breast milk (p-value: 0.081; mean: 134.19; SD: 103.31), breast milk HMF (p-value: 0.081; mean: 119.36; SD: 157.94), formula milk (p-value: 0.081; mean: 163.32; SD: 120.51). There was no significant difference between the type of enteral nutrition provided and the length of stay in both types of enteral breast milk (p-value: 0.256; mean 12.26; SD: 9.61), breast milk HMF (p-value: 0.256; mean: 20.91; SD: 17.277), formula milk (p-value: 0.256; mean: 13.46; SD: 11.877). Conclusion: The highest average weight gain of premature LBW infants was in HMF breast milk nutrition. The average length of the fastest period of care for premature LBW babies is on breast milk nutrition. Suggestions to provide education to pregnant women in optimizing breastfeeding through expressed breast milk for premature LBW babies who are being treated in the hospital. So that it can increase body weight and shorten the period of hospitalization.